Cashew Nut Agroindustry Added Value Analysis: Case Study XYZ Industry in Kendari City - Asriani Asriani; Nurlian Nurlian; Bambang Indra Yuwono (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to determine the added value of cashew nut agroindustry in the Case Study: XYZ Industry in Kendari City. The research in one cashew nut agroindustry, Kadia District, Kendari City. The data collected in this study consisted of two types, namely: primary data and secondary data. The data obtained in this study were tabulated and then analyzed using the analysis of revenue and value-added costs with research variables and business characteristics. The results showed that the cashew nut agroindustry could provide an Rp income. of 72,479,139/month or 47% per production process for one month. The Cashew nut agroindustry provides a gross added value of Rp. 39,216/kg of raw materials and net value added Rp. 38.147/kg of raw materials.